2002
DOI: 10.1002/for.816
|View full text |Cite
|
Sign up to set email alerts
|

A non‐linear dynamic model for multiplicative seasonal‐trend decomposition

Abstract: A non-linear dynamic model is introduced for multiplicative seasonal time series that follows and extends the X-11 paradigm where the observed time series is a product of trend, seasonal and irregular factors. A selection of standard seasonal and trend component models used in additive dynamic time series models are adapted for the multiplicative framework and a non-linear filtering procedure is proposed. The results are illustrated and compared to X-11 and log-additive models using real data. In particular it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Finally, the methodology of Ozaki and Thomson (1994) is close to our non‐linear UC model of below although the specifics and motivations of the models are different. Ozaki and Thomson considered a UC model in levels, given by where M t is a linear Gaussian stochastic process for the trend whereas G t is a stochastic seasonal component.…”
Section: Seasonal Interacting Componentsmentioning
confidence: 97%
“…Finally, the methodology of Ozaki and Thomson (1994) is close to our non‐linear UC model of below although the specifics and motivations of the models are different. Ozaki and Thomson considered a UC model in levels, given by where M t is a linear Gaussian stochastic process for the trend whereas G t is a stochastic seasonal component.…”
Section: Seasonal Interacting Componentsmentioning
confidence: 97%
“…Edmundson (1990), Choi and Wohar (1995), Ozarki and Thompson (2002), and Webby, O'Connor, and Edmundson (2005) found that time‐series forecasts can be significantly improved by decomposing the series into its simplest components: trend, cycle, and noise. Decomposition of a forecasting problem has also been implemented by breaking the problem down into independent components that can be additively recombined.…”
Section: The Practice Of Business Forecastingmentioning
confidence: 99%
“…Finally, the methodology of Ozaki and Thomson (1994) is close to our non-linear UC model of Section 3.2 below although the specifics and motivations of the models are different. Ozaki and Thomson considered a UC model in levels, given by…”
Section: A Review Of Non-linear Trend-seasonal Modelsmentioning
confidence: 99%